Multiple Trophic Tracer Analyses of Subarctic Rhodolith (Lithothamnion glaciale) Bed Trophodynamics Uncover Bottom-Up Forcing and Benthic-Pelagic Coupling - Hacker Teper, Sean; Parrish, Christopher C.; Gagnon, Patrick (Frontiers in Marine Science, 2022)
We paired a survey of cryptofaunal abundance and rhodolith morphology with lipid, fatty acid, and stable isotope analyses to quantify nutritional patterns and trophic linkages of six dominant echinoderm, bivalve, gastropod, and polychaete species, two macroalgal species, seawater, and underlying sediment in a large (>500 m2) rhodolith (Lithothamnion glaciale) bed in southeastern Newfoundland (Canada). We found high densities of chitons (Tonicella marmorea and T. rubra) and daisy brittle star (Ophiopholis aculeata), and overall species composition, rhodolith morphology (shape and size), and total rhodolith biomass were consistent with other studies of the bed, indicating high temporal stability. Our lipid and fatty acid analyses revealed high levels of phospholipids and unsaturated fatty acids combined with low sterols in all animal species, suggesting adaptation for enhanced cell membrane fluidity in a cold-water environment. They also showed that most taxa sampled feed on a shared resource; diatoms, and that (non-kelp) macroalgal detritus are a key food source within rhodolith communities. Our stable isotope analysis uncovered three distinct trophic levels; producers, suspension/filter feeders and grazers, and predators, and unveiled potential resource partitioning between first- (H. arctica) and second- (O. aculeata and Tonicella spp.) order consumers, whereby differences in feeding strategies enable utilization of specific components of the same organic and inorganic material. The unprecedented analytical resolution enabled by the combined use of three trophic tracers indicate that bottom-up forcing (as a mechanism of trophic control) and benthic-pelagic coupling (as a pathway of nutrient and energy flow) operate simultaneously, at least seasonally, in subarctic rhodolith beds.